DESIGN, DEVELOPMENT AND IMPLEMENTATION OF THE MULTIMEDIA TRAINING SYSTEMS OF A MARINE PROFILE DISCIPLINES - Kravtsova Л.В. (Journal of Information Technologies in Education (ITE), 2011)
It is presented the conceptual model of a multimedia program-methodical complex which is the basis of the training system at the course «Management of a sea vessel». On an example of studying of a theme «Stability of a vessel» possibilities of use of spreadsheets Excel and Flash for learning efficiency increase are shown.